SuRxgWell: study protocol for a randomized controlled trial of telemedicine-based digital cognitive behavioral intervention for high anxiety and depression among patients undergoing elective hip and knee arthroplasty surgery - Kaynar, A. Murat; Lin, Charles; Sanchez, Andrea Gomez; Lavage, Danielle R.; Monroe, Amy; Zharichenko, Nicole; Strassburger, Meredith; Saucier, Katheryn; Groff, Yram J.; Klatt, Brian A.; O’Malley, Michael J.; Szigethy, Eva; et al. (Current controlled trials in cardiovascular medicine, 2023)
Mood disorders (anxiety, depression), sleep disorders, and catastrophizing lead to increased post-operative pain perception, increase in postoperative opioid consumption, decreased engagement with physical activity, and increased resource utilization in surgical patients. Psychosocial disorders significantly affect postoperative outcome. Unfortunately, studies focused on perioperative psychological assessment and treatment are scarce. We propose to test whether digital cognitive behavioral intervention (dCBI) can help surgical patients. dCBI such as RxWell™ is a proven treatment for mood disorders in medical patients such as reducing depression in patients with inflammatory bowel disease. We hypothesize that RxWell™ will also be effective in surgical patients. This study aims to test whether RxWell™ can improve preoperative mood disorders and subsequently reduce postoperative pain and opioid requirement in patients scheduled for primary total hip and knee arthroplasty (THA, TKA). We named the trial as the SuRxgWell trial. This is a randomized, controlled trial that will enroll primary and unilateral THA or TKA patients with anxiety and/or depression symptoms before surgery to receive the SuRxgWell dCBI program and investigate its impact on postoperative outcomes including postoperative pain, anxiety, depression, sleep disorder, and catastrophizing. After signing an informed consent, subjects will be screened using the PROMIS questionnaires, and subjects with a T-score of ≥ 60 on the short Patient-Reported Outcomes Measurement Information System (PROMIS) 4a Anxiety and/or short PROMIS 4a Depression questionnaires will be randomized to either usual care (control group) or the cognitive behavioral intervention, RxWell™, plus usual care (intervention group). The control group will receive information on how to locate tools to address anxiety and depression, whereas the intervention group will have access to SuRxgWell 1 month prior to surgery and up to 3 months after surgery. The allocation will be 3:1 (intervention to control). Investigators will be blinded, but research coordinators approaching patients and research subjects will not. The primary outcome will be day of surgery anxiety or depression symptoms measured with the PROMIS Short Form v1.0 -Anxiety 4a/Depression and Generalized Anxiety Disorder Measure (GAD-7) and Patient Health Questionnaire (PHQ-8). Secondary end points include measuring other health-related quality of life outcomes including sleep disturbance, fatigue, ability to participate in social roles, pain interference, cognitive function, pain catastrophizing, and physical function. Other secondary outcomes include collecting data about preoperative and postoperative pain scores, and pain medication usage, and orthopedic functional recovery at baseline, day of surgery, and 1, 2, and 3 months after the surgery with the Pain Catastrophizing Scale, the Knee injury and Osteoarthritis Outcome Score (KOOS), and Hip injury and Osteoarthritis Outcome Score (HOOS). In addition, subjects will be asked to complete a GAD-7 and PHQ-8 questionnaires bi-weekly (via the RxWell™ app for the interventional group or REDCAP for the control group). Data about postsurgical complications, and resource utilization will also be recorded. We will also receive monthly reports measuring the usage and engagement of RxWell use for each participant randomized to that arm. The primary hypotheses will be assessed with intention-to-treat estimates, and differences in primary outcome will be tested using independent two sample t-tests. This trial is registered to the ClinicalTrials.gov database (NCT05658796) and supported by the DAPM, UPMC Health Plan, and the NIH. Our trial will evaluate the feasibility of digital cognitive behavioral intervention as a perioperative tool to improve anxiety and depression before and after major orthopedic surgery in comparison to education. If digital cognitive behavioral intervention proves to be effective, this might have important clinical implications, reducing the incidence of chronic postsurgical pain and improving outcomes.